Human Papillomavirus (HPV) infection awareness and vaccine acceptance among high-risk men in Perak, Malaysia - CI, Noor Syazana; M, Leelavathi; J, Adawiyah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Human Papillomavirus (HPV) causes anogenital warts and malignancies in both men and women. In Malaysia, HPV vaccine is currently available for young girls while men are expected to benefit from herd immunity. However, high-risk men e.g. those who practice homo and bisexual activities may not benefit from this herd immunity. Hence, it is important to assess their awareness of HPV and vaccine acceptance for appropriate counselling on vaccination. The objective of this study was to assess HPV and vaccine awareness, its acceptance, facilitators, and barriers among high-risk men. Men between the ages of 18 to 45 years from the Human Immunodeficiency Virus (HIV) and Sexually transmitted Disease (STD) clinics of a tertiary hospital and six Health Clinics in Perak were invited to participate. HPV awareness, vaccine acceptance, facilitators, and barriers to vaccination were assessed using a self-administered questionnaire. A total of 194 men participated in this study. Only a small percentage of them (35.6%) were aware about HPV and HPV vaccine (21.6%). However, most of them (87.1%) were willing to accept vaccination after receiving the necessary information. Common facilitators for vaccination were doctor’s recommendation (94.3%) government approval (84.5%) and free vaccination (82%) while the most common barriers were cost (68.0%) and side effects of the vaccine (49.5%). Our study showed low-level HPV and vaccine awareness among high-risk men. However, majority of them were willing to accept HPV vaccination. Recommendations from doctors and government approval were the two most important facilitators while cost and side effects were the common barriers to HPV vaccination.